GAMBARAN TINGKAT PENGETAHUAN KELUARGA TENTANG HIPERTENSI DI WILAYAH KERJA UPT PUSKESMAS BAGANSIAPIAPI - Gina Febiola Manalu; Arneliwati Arneliwati; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
One of the non communicable diseases with the most cases and increasing every year is hypertension, hypertensive sufferers are encouraged to take hypertension control efforts to avoid complications. The study aims to describe the level of family knowledge about hypertension in the work area Bagansiapiapi Community Health Center. Method: This study used a descriptive research design with a cross sectional approach. Sample of this study are 87 respondents which selected using accidental sampling techniques. The instrument used are questionnaire that undergone a valid and it is reliable. The analysis of data using univariate analysis. Results: The result of this research showed the majority respondents own knowledge of good are 41 respondents (47,1%). Conclusion: There is family knowledge about hypertension of good, recommendations for families are expected to increase knowledge and support hypertension sufferers in treating hypertension, so that incident of hypertension can be reduced significantly.Keywords : Hypertension, knowledge, non communicable diseases, silent killer